(untitled) (LEARNing Landscapes, 2010)
In Tom Wayman’s poem Did I Miss Anything?, the poet-teacher offers a series of responses to the above question, posed by a student unaware of the always contextual nature of learning. The poet replies:"Nothing" and "Everything." In the course of this paper, I use this poem as a prompt, approaching the tensions held in these words not as a chuckle at the student’s expense, but instead, as a humorous challenge that revisions the question of what is at stake in the educational act, and as an absurd gesturing into the boundaries of what the possibilities of teaching might be.